Primary Gastric Small Cell Carcinoma (Presenting as Linitis Plastica) Diagnosed Using Endoscopic Ultrasound-Guided Biopsy: A Case Report - Ra Ri Cha; Jin Kyu Cho; Wan Soo Kim; Jin Joo Kim; Jae Min Lee; Sang Soo Lee; Hyun Jin Kim (Korean Society of Gastrointestinal Endoscopy, 2019)
Small cell carcinomas are the most aggressive, highly malignant neuroendocrine tumors; among these, gastric small cell carcinoma (GSCC) is extremely rare. Here we report a case of a patient with primary GSCC, presenting as linitis plastic, who was diagnosed using endoscopic ultrasound (EUS)-guided biopsy. With undiagnosed linitis plastica, an 80-year-old woman was referred to our institution. Abdominal computed tomography revealed irregular wall thickening extending from the gastric body to the antrum. Endoscopy suspected to have Borrmann type IV advanced gastric cancer. EUS of the stomach showed diffuse submucosal thickening of the gastric wall, mainly the antrum. EUS-guided bite-on-bite biopsy confirmed the diagnosis of GSCC. In general, GSCC is difficult to diagnose and careful examination is necessary to determine the therapeutic strategy; however, EUS is particularly helpful in the differential diagnosis of a lesion presenting as linitis plastica.